Murine cytomegalovirus reactivation concomitant with acute graft-versus-host disease is controlled by antibodies - Martina Seefried; Nadine Hundhausen; Irena Kroeger; Maike Büttner-Herold; Petra Hoffmann; Matthias Edinger; Evelyn Ullrich; Friederike Berberich-Siebelt; William J. Britt; Michael Mach; Thomas H. Winkler (JCI Insight, 2023)
Reactivation of human cytomegalovirus (HCMV) from latency is a frequent complication following hematopoietic stem cell transplantation (HSCT). The development of acute graft-versus-host disease (GVHD) is a significant risk factor for HCMV disease. Using a murine GVHD model in animals latently infected with murine CMV (MCMV), we studied preventive and therapeutic interventions in this high-risk scenario of HSCT. Mice latently infected with MCMV experienced reactivated MCMV and developed disseminated MCMV infection concomitant with the manifestations of GVHD. Dissemination was accompanied by accelerated mortality. We demonstrate that MCMV reactivation and dissemination was modulated by MCMV-specific antibodies, thus demonstrating in vivo protective activity of antiviral antibodies. However, the efficacy of serum therapy required repetitive doses of high-titer immune serum secondary to the shortened serum half-life of IgG in animals with GVHD. In a complementary approach, treatment of GVHD by adoptive transfer of donor-derived Tregs facilitated production of MCMV-specific antibodies from newly developing donor-derived B cells. Together, our findings strongly suggest that antibodies play a major role in controlling recurrent MCMV infection that follows GVHD, and they argue for reassessing the potential of antibody treatments as well as therapeutic strategies that enhance de novo antibody development against HCMV.